NORMS OF RISE AND FALL OF CIVILIZATIONS IN THE QUR’AN: BENEFICIAL KNOWLEDGE AND JUSTICE AS A MODEL - Islam, Arshad; Taha Al-Alwani, Ruqaia (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2023)
This paper deals with some of the norms of the establishment and emergence of civilizations according to the Qur’an and analyses the components of such norms. The Qur’an gives explicit attention to the laws and norms on which human societies and civilizations are based, directly and indirectly, by telling the stories of peoples in past eras. The Qur’an also emphasizes that giving priority to the pursuit of material aspects and elements of societies while neglecting their religious and moral aspects is a reason for the decline and collapse of civilizations, as was the case with the people of Sheba. This paper clarifies that the most important norms of the establishment of civilizations include focusing attention on beneficial knowledge and instilling the value of justice in society. The study explores some conditions of previous nations that vanished owing to the absence of these two basic elements, as mentioned in the Qur’an. In conclusion, this article argues for further studies of the Quranic approach to the issue of the rise and fall of human civilizations. Contemporary societies need to be enlightened by the Quranic perspectives on the issue in the light of the present human condition.